Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation Dipadu Peta Konsep terhadap Keterampilan Berpikir Kreatif Siswa - Nadia Larasati; Slamet Santosa; Dewi Puspita Sari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The purpose of this research is to know the influence of cooperative learning model of group investigation type combined concept map to student’s creative thinking skill.The research was considered as quasi experiment research with quantitative approach. The population of this research was all of X degree students at SMA Negeri 1 Karanganyar in academic year 2017/2018 consisting of nine classes. The selected sample is class X IPA 6 and X IPA 8 with cluster sampling technique. The research was designed using posttest only with nonequivalent grup design. Learning is carried out in two classes by applying the group investigation model and group investigation model combined concept map. Data collection techniques use essays test, observations, and documentation. Normality and homogeneity test are performed as a requirement of hypothesis test. Hypothesis test used is t test with 5% significance level. Data analysis assisted with SPSS 22. The research procedure includes planning, implementation and data analysis.The result of the research show that cooperative learning model of group investigation type combined concept map influence to student’s creative thinking skill. Aspects of creative thinking skills examined consist of aspects of originality, fluency, flexibility, and elaboration.